A qualitative study of sexual minority young people's experiences of computerised therapy for depression. (June 2015) - Lucassen, Mathijs FG; Hatcher, Simon; Fleming, Theresa M; Stasiak, Karolina; Shepherd, Matthew J; Merry, Sally N
Objective: To describe the experiences of lesbian, gay, bisexual or sexual minority youth who used a form of computerised therapy (Rainbow SPARX) for depression. Methods: 25 adolescents (20 with significant depressive symptoms) who had trialled Rainbow SPARX took part in semi-structured interviews. The general inductive approach was used to analyse interview data. Results: Feedback consisted of five main themes: 'appealing aspects'; 'applying it to real life'; 'things to improve'; 'aspects that did not appeal'; and 'other themes'. Young people suggested that there should be more sexuality-specific ('rainbow') content in the computer program. Seventeen participants thought computerised therapy helped them feel better or less depressed. Conclusions: Consumer perspectives are increasingly being sought and this user input is especially useful for improving services. Our study provides important in-depth feedback on Rainbow SPARX from the perspective of sexual minority youth, and it highlights that computerised therapies can be successfully modified for groups traditionally under-served by mainstream mental health interventions.